A traveling theatre - TREVISAN, Alexandra (2014)
The VII IUA (International Union of Architects) Conference took place in the summer of 1961 in London. It was organized by Riba (Royal Institute of British Architects) and under the general name “Architecture and Technology”, where the debates focused on new architecture materials and techniques. An international student contest under the theme “A Travelling Theatre” was set up at this conference. In the academic year of 1960/61 the Fine Arts Schools of Porto and Lisbon embraced the UIA proposal by giving some of their 4th year students the chance to develop a project for the mentioned contest. In this period, the Fine Arts School of Oporto headmaster’s, the architect Carlos Ramos, was at the same time vice-president of the UIA, since 1959 - he had been elected at the General Assembly that took place in Lisbon, that year. The first prize of the contest was awarded to Spanish student Emilio Perez Piñero. Yet we believe the projects by the architecture students from Porto, the ones we know from the photographs by Teófilo Rego, present solutions, we think deserve a broader approach, so that, the cross-relations among the Carlos Ramos’ school, the proposed program for the contest by the UIA, and the relation with the Portuguese social and cultural context, particularly in the Theatre’s sphere.